2021
DOI: 10.1149/1945-7111/ac3abc
|View full text |Cite
|
Sign up to set email alerts
|

A Simple g-C3N4/TNTs Heterojunction for Improving the Photoelectrocatalytic Degradation of Methyl Orange

Abstract: In this work, highly ordered titanium dioxide nanotube arrays (TNTs) were first prepared by anodic oxidation method. Then, g-C3N4/TNTs heterojunctions were prepared by ultrasonically loading graphitic carbon nitride (g-C3N4) onto the TNTs. The morphology and crystal structure of TNTs and g-C3N4/TNTs were characterized by SEM/TEM and XRD. The photoelectrocatalytic (PEC) degradation of methyl orange (MO) by TNTs and g-C3N4/TNTs was studied in a PEC degradation system. The photocatalytic (PC), electrocatalytic (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The ZnO/Fe 3 O 4 /g-C 3 N 4 -50% composite exhibited a higher photocatalytic activity after five recycles [ 82 ]. Some g-C 3 N 4 composites reported for the efficient PD of MO dye are AgBr:g-C 3 N 4 [ 83 ], g-C 3 N 4 /TNTs heterojunctions [ 84 ], ternary g-C 3 N 4 /ZnO–W/M nanocomposites [ 85 ], g-C 3 N 4 -TiO 2 nanocomposite [ 86 ], CdS/g-C 3 N 4 hybrid nano-photocatalysts [ 87 ], MoO 3 –g-C 3 N 4 composites [ 88 ], g-C 3 N 4 /ZnO composites [ 89 ], CoFe 2 O 4 /g-C 3 N 4 nanocomposites [ 90 ], g-C 3 N 4 /Bi 4 O 5 I 2 [ 91 ], ternary g-C 3 N 4 /Ag/γ-FeOOH photocatalysts [ 92 ], etc. Some g-C 3 N 4 -based composites/nanocomposites used for the efficient PD of MO dye are consolidated in Table 1 .…”
Section: Composites and Heterojunctionsmentioning
confidence: 99%
“…The ZnO/Fe 3 O 4 /g-C 3 N 4 -50% composite exhibited a higher photocatalytic activity after five recycles [ 82 ]. Some g-C 3 N 4 composites reported for the efficient PD of MO dye are AgBr:g-C 3 N 4 [ 83 ], g-C 3 N 4 /TNTs heterojunctions [ 84 ], ternary g-C 3 N 4 /ZnO–W/M nanocomposites [ 85 ], g-C 3 N 4 -TiO 2 nanocomposite [ 86 ], CdS/g-C 3 N 4 hybrid nano-photocatalysts [ 87 ], MoO 3 –g-C 3 N 4 composites [ 88 ], g-C 3 N 4 /ZnO composites [ 89 ], CoFe 2 O 4 /g-C 3 N 4 nanocomposites [ 90 ], g-C 3 N 4 /Bi 4 O 5 I 2 [ 91 ], ternary g-C 3 N 4 /Ag/γ-FeOOH photocatalysts [ 92 ], etc. Some g-C 3 N 4 -based composites/nanocomposites used for the efficient PD of MO dye are consolidated in Table 1 .…”
Section: Composites and Heterojunctionsmentioning
confidence: 99%
“…Photoelectrocatalytic oxidation of MO using TiO2 nanotube (NT) heterostructures was demonstrated in works (Deng et al 2018;Zeng et al 2021). The results of the studies showed that heterostructures exhibit higher activity during electrocatalysis (EC), photocatalysis (PC), and photoelectrocatalysis (PEC) than the initial TiO2 NTs.…”
Section: Photoelectrocatalytic Oxidationmentioning
confidence: 99%
“…The oxidative decomposition method involves adding strong oxidants directly to water to react with organic matter, thereby achieving the purpose of decomposing it [5]. Catalytic degradation mainly includes photocatalysis [6][7][8][9][10] and electrocatalysis [11][12][13].…”
Section: Introductionmentioning
confidence: 99%